Contribution to the knowledge of Medicinal plants used in the Treatment of Arterial Hypertension by traditional Practitioners Bouar in CAR - Kamba, Francklin; Wei, Shiqiang; Roger, Apema Alimasi Kitete; Olivia, Semboli (Advances in Social Sciences Research Journal, 2016)
This research was conducted in Bouar (Nana, Mambere). The city is located 450 km away from Bangui the capital city of Central African Republic. Bouar is a mountainous city is covered by the Yade Mountains. It is between 15 ° and 16 ° east longitude and between 6 ° and 7 ° of latitude north with an area of 26,600 km2. The Bouar city occupies relatively the entire Northwest Territory, sharing border with the Republic of Cameroon and comprises about 5% of the total population. Census of the area population took place in December 2003 which was 172.754 habitants, with a density population on average of 8.8 to 10 inhabitants per km2. Bouar city is endowed with immense natural resources and varied rainfall, rich soils and a basement of mining, a diverse and abundant wildlife, and a diversity of savanna. Despite all these potentials, Bouar is in a continuous cycle of impoverishment. Socio-sanitary situation continues to deteriorate, access to health care is very difficult, life has become increasingly complex with varied needs and people expect favorable actions from their leaders and efficiency in meeting their immediate needs based on the improvement of their health conditions. The objective of this paper is assessment of medicinal plants used as medicines in the treatment of hypertension in Bouar. Ethno botanical method is recognized as the safest and least expensive method of plant-based drugs on the one hand, but also to help poor farmers who can not afford modern drugs on the other. Bouar has nineteen (19) medicinal species that have been identified and belong to 14 different families with a predominance of Magnoliopsida (Dicotyledonous) on 19 species, 10 are not in the visible flora. This paper is an avenue of our modest contribution to knowledge on medicinal plants used for the treatment of sion in Bouar (Aloe vera, Voacanga africana Lophira lanceolata, Zea mays, Bambusa vulgaris, Elaeis guineensis, Bridelia ferrugenea Protea madiannesis, Lycopersicum esculentum and Capsicum Annuun). Furthermore other hypertension, treating plants are Aloe vera which treats diabetes and the madianensis protea that is used to treat epilepsy, malaria and fever. These plants are commonly used in the treatment of hypertension and other related diseases